Transformasi Digital Pembelajaran Bahasa Arab: Tinjauan Literatur Sistematis terhadap Pemanfaatan Teknologi dari Aplikasi Seluler hingga Kecerdasan Buatan - Julham Hukom (CV. SINAR HOWUHOWU, 2026)
The use of technology in Arabic language learning is growing rapidly alongside the digital transformation of education, but a comprehensive mapping of technology types and their impacts remains scattered. This study aims to map the trends, types, and contributions of technology in Arabic language learning through a systematic literature review. A search of national and international journal databases was conducted using strict inclusion and exclusion criteria, resulting in a selection of 20 articles published between 2017 and 2026. The results of the thematic analysis revealed five dominant technology categories: artificial intelligence and chatbots, augmented reality, mobile applications (mobile-assisted language learning), gamification and interactive quizzes, multimedia, e-learning, and teacher competency. Quasi-experimental empirical findings consistently demonstrated improvements in vocabulary mastery, structural understanding, motivation, and learning engagement. However, technology integration is still limited by infrastructure, teacher readiness and competency, and the need for pedagogical support. This study concludes that technology plays a role as a catalyst for more adaptive, interactive, and personalized Arabic language learning, provided it is accompanied by strengthening teacher competency and a clear pedagogical framework.